LCL161 enhances expansion and survival of engineered anti-tumor T cells but is restricted by death signaling - Afsahi, Arya; Silvestri, Christopher M.; Moore, Allyson E.; Graham, Carly F.; Bacchiochi, Kaylyn; St-Jean, Martine; Baker, Christopher L.; Korneluk, Robert G.; Beug, Shawn T.; LaCasse, Eric C.; Bramson, Jonathan L. (Frontiers in Immunology, 2023)
Background The genesis of SMAC mimetic drugs holds roots in the observation that many cancers amplify IAP proteins to facilitate their survival, and that removal of these pathways would re-sensitize them towards apoptosis. It has become increasingly clear that SMAC mimetics also interface with the immune system in a modulatory manner. Suppression of IAP function by SMAC mimetics activates the non-canonical NF-κB (ncNF-κB) pathway and can augment T cell function, which opens the possibility of using SMAC mimetics to enhance immunotherapeutics. Methods We have investigated the SMAC mimetic LCL161, which promotes degradation of cIAP-1 and cIAP-2, as an agent for delivering transient costimulation to engineered BMCA-specific TAC T cells. In doing so we also sought to understand the cellular and molecular effects of LCL161 on T cell biology. Results LCL161 activated the ncNF-κB pathway and enhanced antigen-driven TAC T cell proliferation and survival. Transcriptional profiling from TAC T cells treated with LCL161 revealed differential expression of costimulatory and apoptosis-related proteins, namely CD30 and FAIM3. We hypothesized that regulation of these genes by LCL161 may influence the drug’s effects on T cells. We reversed the differential expression through genetic engineering and observed impaired costimulation by LCL161, particularly when CD30 was deleted. While LCL161 can provide a costimulatory signal to TAC T cells following exposure to isolated antigen, we did not observe a similar pattern when TAC T cells were stimulated with myeloma cells expressing the antigen target. We questioned whether FasL expression by myeloma cells may antagonize the costimulatory effects of LCL161. Fas-KO TAC T cells displayed superior expansion following antigen stimulation in the presence of LCL161 suggesting a role of Fas-related T cell death in limiting the magnitude of the T cell response to antigen in the presence of LCL161. Conclusions Our results demonstrate that LCL161 provides costimulation to TAC T cells exposed to antigen alone, however LCL161 did not enhance TAC T cell anti-tumor function when challenged with myeloma cells and may be limited due to sensitization of T cells towards Fas-mediated apoptosis.